INFLUENCE DES FUITES D’EAU POTABLE AU RESEAU DE DISTRIBUTION SUR LE CHIFFRE D’AFFAIRES REALISE PAR LA REGIDESO A KINDU DE 2014 A 2020 - ABAVUME, TAMBWE (IJRDO - Journal of Business Management, 2022)
This research is motived by the permanence along the drinking water distribution network of a large number of unrepaired leaks, suggesting that these cannot significandly influence the turnover achieved by REGIDESO in Kindu. Thus, our main concern is to verify the existence or not of a significant link between these leasks and its tornover. The analysis and interpretation of our results reveal that during the 7 years selected for this study, the drinking water leaks identified along the REGIDESO distribution network in Kindu did not significantly influence its turnover. Despite the insignificant impact of water leaks on turnover, the leaks must be repaired, not only in order to reduce consumption bills for subscribrers billed at a flat rate, but also to protect subscribers from illnesses waterborne, because they are the entry points for microbes of all kinds into the distribution network during low pressure hours.